IDENTIFIKASI DAN PENETAPAN KADAR RHODAMIN B DALAM KERUPUK BERWARNA MERAH YANG BEREDAR DI PASAR ANTASARI KOTA BANJARMASIN - Eka Kumalasari (Jurnal Ilmiah Manuntung, 2015)
Crackers are made from tapioca flour batter mixed with flavorings and colorings, still many outstanding crackers that contain ingredients banned dye Rhodamine B. Rhodamine B is a chemical used for red dye in the textile industry and plastic. Rhodamine B can cause cancer, poisoning, lung irritation, sore eyes, and sore throat. This study aims to identify and determination the levels of Rhodamine B in circulating red crackers Antasari market Banjarmasin.The population is that sold in the red crackers that sold in Antasari market Banjarmasin.. The sampling is technique incidental sampling , that is based on chance, so any population by chance met with researchers can be used as a sample. Identification of Rhodamine B was done by Thin Layer Chromatography (TLC) by using the stationary phase silica GF 254 and mobile phase is elution solvent is n-butanol, ethyl acetate, ammonia (10:4:5). Then detected with a UV lamp 254 nm and 366 nm. While for the determination of levels using Vis spectrophotometry at a wavelength of 544 nm.The results showed that the samples of 6 found one sample containing Rhodamine B, namely samples 5 (cassava crackers matches) and obtained values of 7,25 ± 3,8640 levels mg / kg. Based on these results, Rhodamine B still found in crackers that sold in the market Antasari Banjarmasin.